Status Hukum Privatisasi Anak Perusahaan Badan Usaha Milik Negara Di Bidang Usaha Sumber Daya Alam (Perkara Nomor 61/PUU-XVIII/2020): The Legal Standing Regarding Privatization Of Subsidiary Of State-Owned Enterprises In Natural Resources (A Juridical Analysis of the Case Number 61/PUU-XVIII/2020) - Nugroho, Hayyu Rahmanda Adi; Dewantara, Reka; Suwardiyati, Rumi (WARKAT, 2023)
This research departs from the regulatory provisions regarding privatization of a subsidiary under State-owned Enterprises that are deemed to have a legal loophole that may lead to multiinterpretations because the existing regulation has not specifically governed this matter. Privatization of the subsidiary as mentioned above is intended to give legal protection to the members of the public in line with the statement ‘natural resources are controlled by the state for the benefits of the people’. With normative-juridical methods, statutory, case, and analytical approaches, this research aims to investigate whether the subsidiary under the State-owned Enterprises can be privatized by the Government and how the synchronization of the regulation governing privatization towards the State-owned Enterprises in natural resources is performed. The primary and secondary materials were analyzed using the library technique. The analysis referred to the A Contrario argumentative technique and systematic interpretation technique. This research concludes that the subsidiary under the state-owned Enterprises can be privatized as long as it does not deactivate the authority of the state to control the subsidiary to ensure that this approach is not deviating from the objective to bring the welfare to the people. Not only can the concept of the control of the state be seen based on private ownership but it may also involve policies, administration, regulation, management, and supervision for the welfare of all people.